L’écrit réflexif en formation initiale : entre prise de risque, construction de soi et assise professionnelle - Céline Chauvigné (Éducation et Socialisation)
The research focuses on identity and professional construction and skills acquisition among inexperienced supervisors during their year training at institute (Institut Universitaire de Formation des Maîtres) in France. It is through writing and especially the professional report that we try to show why it remains a major element in the training process. However, it is subject to various tensions in its context is not always the desired effect. The explementation at the « I.U.F.M. Pays de la Loire » as a framework to address the writing, its position and approach by inexperienced supervisors before considering coaching, challenges and contributions.